Steganography based on least significant bit method was designed for digital image with lossless compression technique - Wiryawan, I Gede; Sariyasa; Gunadi, I Gede Aris (2018 International Conference on Signals and Systems (ICSigSys), 2018)
Many digital media that can be used as cover in steganography, such as image, audio, and video. The most frequently used media is image. Compression technique for digital image can be differentiated into two, i.e. lossy and lossless compression techniques. In lossless compression technique there are some algorithms, which include Run Length Encoding algorithm in file Bitmap Picture Format, Lempel-Ziv-Welch in Graphic Interchange Format, and LZW algorithm which is combined with Huffman Encoding algorithm in Portable Network Graphics Format This lossless compression technique is more suitably implemented in steganography method in spatial domain, with its competitive advantage in payload capacity. In this study digital image with three file formats were used in steganography method in spatial domain, i.e. Least Significant Bit. The aim was to find out the comparison among the three by testing the change in quality and the characteristics that occur. The result, digital image with BMP and PNG file formats which identical values after assessing the quality change (Image Quality Assessment) and characteristic change. From the testing the MSE value of 7.674×10 −6 and PSNR value of 99.3147 dB were found. The change in characteristic values obtained from the characters testing was very small, i.e. changes in the values for Mean, Standard Deviation and Entropy are 1.31×10 −4 , 2.18×10 −5 , and 0.0012. For the future, steganography method in two different domains can be combined and to find a better level of security they can also be combined with cryptography.